Report of the Commission on Genetic Resources for Food and Agriculture - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2011)
The Thirteenth Regular Session of the Commission on Genetic Resources for Food and Agriculture (Commission) met in Rome, Italy, from 18 to 22 July 2011. The list of delegates and observers is available on the Commission’s web site.